Preparation and Evaluation of Carbamazepine Sustained Release Tablets - Saha, Shib Sankar; Nazmi, Mehrina; Saha, Nandini; Reza, Md Selim (Dhaka University Journal of Pharmaceutical Sciences, 2013)
The purpose of the present studies was to develop and characterize sustained release tablets of Carbamazepine, an antiepileptic drug. Tablets were prepared by direct compression method. In the formulation, the active drug was taken 200 mg in every formulation. Methocel K4M, Methocel K15M CR, Methocel K100LV CR, Eudragit RSPO and Eudragit RLPO polymers were used as rate retarding agents in twenty four formulations (F-1 to F-24). The effect of hydrophilic polymer PEG 6000 as channeling agent with Methocel K4M was observed in four formulations (F-5 to F-8). The granules were evaluated for angle of repose, bulk density, tapped density. The tablets were subjected to average weight, diameter, thickness, weight variation, hardness, friability and in vitro dissolution studies. The granules showed satisfactory flow properties, compressibility and drug content. The in vitro dissolution study was carried using USP Apparatus-I (Rotating basket method apparatus) for 6 to 12 hours in distilled water with 1% sodium lauryl sulphate as the dissolution medium. The release mechanisms were explored and explained by Zero order, First order, Higuchi, Korsmeyer-Peppas and Hixson-Crowell equations. Primarily twelve formulations were prepared by using four variable amount of three polymers; Methocel K4M (50, 100, 150 and 200 mg) in the formulations from F-1 to F-4, Methocel K15M CR (50, 100, 150 and 200 mg) in the formulations from F-9 to F-12 and Methocel K100LV CR (50, 100, 150 and 200 mg) in the formulations from F-13 to F-16. Then four formulations were prepared where Methocel K4M amount was same but using variable amount of hydrophilic polymer PEG 6000 (50, 100, 150 and 200 mg). After that another eight formulations were prepared by using polymer Eudragit RSPO and Eudragit RLPO by using variable amount. In F-17 to F-20 the use of Eudragit RSPO was in variable amount (50, 100, 150 and 200 mg) and in F-21 to F-24 the use of Eudragit RLPO was in variable amount (50, 100, 150 and 200 mg). Other excipients remained same in the formulations. Among these twenty four formulations sustainability was studied and compared with three market product of 200 mg tablet. It was found that effect of PEG 6000 as channeling agent subsequently decreased the sustaining action (Formulation F5-F8). DOI: http://dx.doi.org/10.3329/dujps.v11i2.14577 Dhaka Univ. J. Pharm. Sci. 11(2): 173-180, 2012 (December)